2007
DOI: 10.1128/aem.00863-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Cadmium-Inducible Hansenula polymorpha SEO1 Gene Promoter by Transcriptome Analysis and Its Application to Whole-Cell Heavy-Metal Detection Systems

Abstract: The genomewide gene expression profiling of the methylotrophic yeast Hansenula polymorpha exposed to cadmium (Cd) allowed us to identify novel genes responsive to Cd treatment. To select genes whose promoters can be useful for construction of a cellular Cd biosensor, we further analyzed a set of H. polymorpha genes that exhibited >6-fold induction upon treatment with 300 M Cd for 2 h. The putative promoters, about 1,000-bp upstream fragments, of these genes were fused with the yeast-enhanced green fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…These results revealed that the JLP1 promoter is more appropriate than the SEO1 promoter that was used in the reporter assay strain by Park et al (2007). The greater Cd-induced transcription of lacZ from the JLP1 promoter than the SEO1 promoter in this study is supported by the findings of a yeast microarray study (Momose and Iwahashi, 2001).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These results revealed that the JLP1 promoter is more appropriate than the SEO1 promoter that was used in the reporter assay strain by Park et al (2007). The greater Cd-induced transcription of lacZ from the JLP1 promoter than the SEO1 promoter in this study is supported by the findings of a yeast microarray study (Momose and Iwahashi, 2001).…”
Section: Resultssupporting
confidence: 77%
“…The promoter sequences of the CUP1, SEO1, and UFO1 genes have been used to detect heavy metals. Yeast strains possessing CUP1 reporter plasmids respond to copper (Cu) and cadmium (Cd) (Tohoyama et al, 1992), those possessing the SEO1 reporter respond to Cd, arsenic (As), and mercury (Hg) (Park et al, 2007), and those possessing the UFO1 reporter respond to arsenate and ultraviolet light B (UVB) (Bakhrat et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These systems have been used as tools for studying the molecular regulation of target gene expression and protein production of genes in industrial fungi (20,39). Further, recombinant bacterial and fungal strains that possess a metal-inducible promoter have been used as biosensors for monitoring heavy metal contamination (25,33). A woundinducible promoter was also recently used to generate transgenic plants that can recognize fungal infections (36).…”
mentioning
confidence: 99%
“…Regulation of gene expression by conditional promoters, including copper-, cadmium-, thiamine-, and alcohol-responsive promoters, has been developed in various organisms (23,25,30,(34)(35). These systems have been used as tools for studying the molecular regulation of target gene expression and protein production of genes in industrial fungi (20,39).…”
mentioning
confidence: 99%
“…Until recently, it was considered that the sequestration of this heavy metal in H. polymorpha occurs similarly to that found in Saccharomyces cerevisiae (with glutathione being the main cd intracellular chelator), but different from Schizosaccharomys pombe and Candida glabrata (27). however, several papers report identification of cadmium-ion tolerant Hansenula species (31,44), suggesting that much profounder investigations should be made on the cadmium tolerance of these yeast microorganisms.…”
Section: Oxygen Metabolism Affects Growth On CDmentioning
confidence: 99%